(untitled) (Scientific journal of the Fergana State University, 2026)
The Chortoqsoy River is located in the northeastern part of the Fergana Valley and has a total length of 82.5 km. The study identified 12 fish species belonging to 3 orders, 7 families, and 11 genera. Among them, 41.7% are native and endemic, while 58.3% are invasive species. The record of Triplophysa ferganaensis indicates an expansion of its distribution range. These preliminary findings provide an important scientific basis for assessing the species diversity of the Chortoqsoy River ichthyofauna, analyzing their distribution patterns, and supporting further comprehensive ichthyological investigations.